Pengaruh Konflik Kerja, Lingkungan Kerja dan Komunikasi Terhadap Kinerja Karyawan pada KPRI Sedar Ngancar - Sazuan Prasetyo; H. Moch. Saleh Udin; Trisnia Widuri (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to determine the influence of the variables work conflict (X1), work environment (X2), and communication (X3) on employee performance (Y) at KPRI Sedar Ngancar. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the saturated sampling method, the number of samples in the study was 36 respondents at KPRI Sedar Ngancar. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The research results showed that the multiple linear regression equation Y= 1.564 + 0.688X1 + 0.584X2 + 0.343X3 and the results of the t test for the work conflict, work environment and communication variables had a partially significant effect on employee performance with sig < 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that work conflict, work environment and communication simultaneously have a significant effect on the performance of KPRI Sedar Ngancar employees.